(untitled) (Revista Electrónica Calidad en la Educación Superior, 2025)
In a constantly changing society, innovative, inclusive, and meaningful learning contexts are needed. The Biological Sciences Department has been improving its teaching practices and the didactic resources it uses in its courses, where ongoing training, collaborative work networks, and teacher analysis and reflection have been essential. This essay aims to analyze the process of change in the development of resources, highlighting their impact on distance education. Over the past five years, approximately 60 new didactic tools have been created to support teaching and learning processes, while also strengthening students’ scientific competencies. These improvement strategies have played a crucial role in enhancing changes in teaching mediation and the implementation of didactic strategies.